Sistem Informasi Penjualan Harian Berbasis Web sebagai Solusi Digitalisasi Pencatatan Keuangan UMKM - Budiman Budiman; Entin Sutinah; Nani Agustina (Program Studi Informatika Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2026)
Micro, Small, and Medium Enterprises (MSMEs) often face challenges in managing transaction records and financial reports manually, which can lead to recording errors and reduced operational efficiency. This study aims to develop a web-based daily sales information system to manage sales transactions, product data, income, expenses, and profit-loss reports in an integrated manner. The system was developed using the Waterfall method and web-based technology. The results show that the system can assist MSMEs in recording transactions digitally, improving data accuracy, accelerating financial report preparation, and supporting more effective and efficient business decision-making.